2017
DOI: 10.1371/journal.pone.0179182
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided cable-free 13-gauge vacuum-assisted biopsy of non-mass breast lesions

Abstract: PurposeTo compare the outcomes of ultrasound-guided core biopsy for non-mass breast lesions by the novel 13-gauge cable-free vacuum-assisted biopsy (VAB) and by the conventional 14-gauge semi-automated core needle biopsy (CCNB).Materials and methodsOur institutional review board approved this prospective study, and all patients provided written informed consent. Among 1840 ultrasound-guided percutaneous biopsies performed from August 2013 to December 2014, 145 non-mass breast lesions with suspicious microcalci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…A single preliminary study [46] on a cable-free VABB system reported potential disadvantages in the diagnosis of non-nodular lesions (non-mass). Successive studies in literature on comparable systems to the present study [25,37,[46][47][48][49][50][51] have not shown any significant differences in terms of sensitivity, specificity, and diagnostic accuracy compared to the traditional VABB using an 8-11G needle but only a greater underestimation and a larger number of FNs [25], probably correlated to the gauge of the smaller needle.…”
Section: Discussionmentioning
confidence: 43%
“…A single preliminary study [46] on a cable-free VABB system reported potential disadvantages in the diagnosis of non-nodular lesions (non-mass). Successive studies in literature on comparable systems to the present study [25,37,[46][47][48][49][50][51] have not shown any significant differences in terms of sensitivity, specificity, and diagnostic accuracy compared to the traditional VABB using an 8-11G needle but only a greater underestimation and a larger number of FNs [25], probably correlated to the gauge of the smaller needle.…”
Section: Discussionmentioning
confidence: 43%
“…Our experimental results show that elite biopsy has a higher pathological accuracy rate and lower underestimation rate than core needle biopsy. There is no significant difference in pathological accuracy rate and underestimation rate between the Mammotome and elite biopsy group, as other experimental studies have revealed [11,19]. It is safe to operate without special equipment, it is easy and simple to operate, and is not limited by the environment.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, we originally addressed the topic of non-mass lesions in the context of SLL, a term not present in the BI-RADS ® lexicon, but which has been much discussed in more recent articles, and which is still little recognized by radiologists in general. 20,22,36,37 SLL is indeed one of the main benign representatives of this group of lesions.…”
Section: Discussionmentioning
confidence: 99%